Possibilities and challenges of a large international benchmarking in pediatric diabetology—The SWEET experience. (October 2016) - Witsch, Michael; Kosteria, Ioanna; Kordonouri, Olga; Alonso, Guy; Archinkova, Margarita; Besancon, Stephane; Birkebæk, Niels H.; Bratina, Natasa; Cherubini, Valentino; Hanas, Ragnar; Hasnani, Dhruvi; Iotova, Violeta; et al.
Abstract : Aim: Despite the existence of evidence‐based guidelines for the care of children with diabetes, widespread gaps in knowledge, attitude, and practice remain. The purpose of this paper is to present a review of benchmarking practices and results of this process within SWEET, moreover focusing on current challenges and future directions. Methods: Biannually, members electronically transfer de‐identified clinic data for 37 parameters to the SWEET database. Each center receives benchmarking and data validation reports. Results: In 2015, 48 centers have contributed data for 20 165 unique patients (51.6% male). After exclusion for missing data 19 131 patients remain for further analysis. The median age is 14.2 years, with a median diabetes duration 4.8 years; 96.0% of patients have type 1, 1.1% type 2, and 2.9% other diabetes types. Data completeness has increased over time. In 2015, median HbA1c of all patients' (diabetes type 1) medians was 7.8% (61.7 mmol/mol) with 39.1%, 41.4%, and 19.4% of patients having HbA1c < 7.5% (58 mmol/mol), 7.5%–9% (58–75 mmol/mol) and >9% (75 mmol/mol), respectively. Although HbA1c has been stable over time [7.7%–7.8% (60.7–61.7 mmol/mol)], there remains wide variation between centers. Fourteen centers achieve a median HbA1c <7.5% (58 mmol/mol). Conclusions: Our vision is that the participation in SWEET is encouraging members to deliver increasingly accurate and complete data. Dissemination of results and prospective projects serve as further motivation to improve data reporting. Comparing processes and outcomes will help members identify weaknesses and introduce innovative solutions, resulting in improved and more uniform care for patients with diabetes.